Análisis de la metodología utilizada por los docentes de matemática de La Unidad Educativa Víctor Proaño Carrión, periodo 2016 – 2017. - Cacoango Morocho, Erika Alexandra (2018)
A society´s development in the result of the solid platform of education, so that, educational action promotes student training, the transmission of knowledge, ways of acting, qualities, skills, competences, etc. In this regard, it is relevant to consider the work performed by teachers, the methodology used, and the pedagogical models. Reason why we develop the research whose goal is in the identification of the methodology used by mathematics teachers, of the Victor Proaño Carrión, by applying a questionnaire to analyze the results obtained. The type of descriptive, explanatory, bibliographical, and field research was used, with a level of exploratory research, which allowed to determine the pedagogical models on which the teacher's methodology is based. The design of the research is non-experimental because no variable was manipulated, in addition, all the teachers that make up the population were considered, the same ones who were subjected to the techniques and evaluation instruments, to subsequently undertaken the analysis and interpretation of the data obtained, and finally the conclusions and recommendations were made, where it was determined that a large number of teachers use the behavioral pedagogical model, followed by the traditional pedagogical one and the constructivist pedagogical model, based on the results. it is recommended to use in a flexibility way teaching methodology, in function and constancy of the pedagogical models, needs, and educational requirements.